Metagenomic insights to understand transient influence of Yamuna River on taxonomic and functional aspects of bacterial and archaeal communities of River Ganges - Samson, Rachel; Shah, Manan; Yadav, Rakeshkumar; Sarode, Priyanka; Rajput, Vinay; Dastager, Syed G.; Dharne, Mahesh S.; Khairnar, Krishna (Science of the Total Environment, 2019)
River confluences are interesting ecosystems to investigate for their microbial community structure and functional potentials. River Ganges is one of the most important and holy river of India with great mythological history and religious significance. The Yamuna River meets Ganges at the Prayagraj (formerly known as Allahabad), India to form a unique confluence. The influence of Yamuna River on taxonomic and functional aspects of microbiome at this confluence and its downstream, remains unexplored. To unveil this dearth, whole metagenome sequencing of the microbial (bacterial and archaeal) community from the sediment samples of December 2017 sampling expedition was executed using high throughput MinION technology. Results revealed differences in the relative abundance of bacterial and archaeal communities across the confluence. Grouped by the confluence, a higher abundance of Proteobacteria and lower abundance of Bacteroidetes and Firnacutes was observed for Yamuna River (G15Y) and at immediate downstream of confluence of Ganges (G15DS), as compared to the upstream, confluence, and farther downstream of confluence. A similar trend was observed for archaeal communities with a higher abundance of Euryarchaeoto in G15Y and G15DS, indicating Yamuna River's influence. Functional gene(s) analysis revealed the influence of Yamuna River on xenobiotic degradation, resistance to toxic compounds, and antibiotic resistance interceded by the autochthonous microbes at the confluence and succeeding downstream locations. Overall, similar taxonomic and functional profiles of microbial communities before confluence (upstream of Ganges) and farther downstream of confluence, suggested a transient influence of Yamuna River. Our study is significant since it may be foundational basis to understand impact of Yamuna River and also rare event of mass bathing on the microbiome of River Ganges. Further investigation would be required to understand, the underlying cause behind the restoration of microbial profiles post-confluence farther zone, to unravel the rejuvenation aspects of this unique ecosystem. (C) 2019 Elsevier B.A. All rights reserved.
Keywords: Confluence zone; Ganges; Metagenomics; Transient influence; Yamuna

Comprehensive metagenomic insights into a unique mass gathering and bathing event reveals transient influence on a riverine ecosystem - Yadav, Rakeshkumar; Rajput, Vinay; Gohil, Kushal; Khairnar, Krishna; Dharne, Mahesh (Ecotoxicology and Environmental Safety, 2020)
The religious mass gathering and bathing can pose a multitude of significant public health challenges and lead to severe alterations in the river microbial ecology. The Pandharpur Wari is an annual pilgrimage of Maharashtra, India, where millions of devotees carry the footprints of the saint-poets and pay their obeisance to Lord Vitthal on the 11th day of moon's waxing phase (Ashadi Ekadashi). As a part of the ritual, the engrossed devotees, walk over 250 km, take a first holy dip in a sacred river Indrayani at Alandi and secondly in Bhima River at Pandharpur. The MinION-based shotgun metagenomic approach was employed to examine the impact of spiritual mass bathing on environmental changes (concerning the river microbial community structure and functions); and public health aspects (in terms of changes in the pathogenic potential and antibiotic resistance). The analysis of bathing and post-bathing samples of both the rivers revealed alterations in the alpha and beta diversity, indicating significant spatiotemporal variations in the overall microbial structure and function. Furthermore, the analysis revealed up to 80% of differences in the abundance of virulence genes between the bathing and post bathing samples. We observed parallel increase of priority skin and enteric pathogens (ranging from 11% to 80%) such as Acinetobacter baumannii, Staphylococcus aureus, Streptococcus pyogenes, Mycobacterium tuberculosis, and Pseudomonas aeruginosa during the bathing event. Moreover, we observed a significant increase in the antibiotic resistance in the bathing samples of Bhima and Indrayani rivers respectively. Altogether, this is the first comprehensive metagenomic study unravelling the influence of religious mass-bathing on the riverine ecosystem.
Keywords: Antibiotic resistance; Mass bathing; MinION sequencing; Priority pathogens; Virulence genes

Deciphering taxonomic and functional diversity of fungi as potential bioindicators within confluence stretch of Ganges and Yamuna Rivers, impacted by anthropogenic activities - Samson, Rachel; Rajput, Vinay; Shah, Manan; Yadav, Rakeshkumar; Sarode, Priyanka; Dastager, Syed G.; Dharne, Mahesh S.; Khairnar, Krishna (Chemosphere, 2020)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">River confluences are interesting ecological niche with limited information in respect of the structure and the functions of diverse microbial communities. Fungi are gaining global attention as promising biological spectacles for defining the trophic status of riverine systems. We condense existing knowledge in confluence diversity in two Indian rivers (i.e. Ganges and Yamuna), by combining sediment metagenomics using long read aided MinION nanopore sequencing. A total of 63 OTU’s were observed, of which top 20 OTU’s were considered based on relative abundance of each OTU at a particular location. Fungal genera such as <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Aspergillus, Penicillium<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">, <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Kluveromyces, Lodderomyces,<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Nakaseomyces<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> were deciphered as potential bio indicators of river pollution and eutrophication in the confluent zone. <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">In silico<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> functional gene analysis uncovered hits for neurodegenerative diseases and xenobiotic degradation potential, supporting bioindication of river pollution in wake of anthropogenic intervention.

Insights from a pan India Sero-epidemiological survey (Phenome-India Cohort) for SARS-CoV2 - Naushin, Salwa; Sardana, Viren; Ujjainiya, Rajat; Bhatheja, Nitin; Kutum, Rintu; Bhaskar, Akash Kumar; Pradhan, Shalini; Prakash, Satyartha; Khan, Raju; Rawat, Birendra Singh; Tallapaka, Karthik Bharadwaj; Anumalla, Mahesh; et al. (eLife, 2021)
To understand the spread of SARS-CoV2, in August and September 2020, the Council of Scientific and Industrial Research (India) conducted a serosurvey across its constituent laboratories and centers across India. Of 10,427 volunteers, 1058 (10.14%) tested positive for SARS-CoV2 anti-nucleocapsid (anti-NC) antibodies, 95% of which had surrogate neutralization activity. Three-fourth of these recalled no symptoms. Repeat serology tests at 3 (n = 607) and 6 (n = 175) months showed stable anti-NC antibodies but declining neutralization activity. Local seropositivity was higher in densely populated cities and was inversely correlated with a 30-day change in regional test positivity rates (TPRs). Regional seropositivity above 10% was associated with declining TPR. Personal factors associated with higher odds of seropositivity were high-exposure work (odds ratio, 95% confidence interval, p value: 2.23, 1.92-2.59, <0.0001), use of public transport (1.79, 1.43-2.24, <0.0001), not smoking (1.52, 1.16-1.99, 0.0257), non-vegetarian diet (1.67, 1.41-1.99, <0.0001), and B blood group (1.36, 1.15-1.61, 0.001).

Metagenomic mining of Indian river confluence reveal functional microbial community with lignocelluloytic potential - Rajput, Vinay; Samson, Rachel; Yadav, Rakeshkumar; Dastager, Syed; Khairnar, Krishna; Dharne, Mahesh (3 Biotech, 2022)
Microbial carbohydrate-active enzymes (CAZyme) can be harnessed for valorization of Lignocellulosic biomass (LCB) to value-added chemicals/products. The two Indian Rivers Ganges and the Yamuna having different origins and flow, face accumulation of carbon-rich substrates due to the discharge of wastewater from adjoining paper and pulp industries, which could potentially contribute to the natural enrichment of LCB utilizing genes, especially at their confluence. We analyzed CAZyme diversity in metagenomic datasets across the sacred confluence of the Rivers Ganges and Yamuna. Functional annotation using CAZyme database identified a total of 77,815 putative genes with functional domains involved in the catalysis of carbohydrate degradation or synthesis of glycosidic bonds. The metagenomic analysis detected similar to 41% CAZymes catalyzing the hydrolysis of lignocellulosic biomass polymers- cellulose, hemicellulose, lignin, and pectin. The Beta diversity analysis suggested higher CAZyme diversity at downstream region of the river confluence, which could be useful niche for culture-based studies. Taxonomic origin for CAZymes revealed the predominance of bacteria (97%), followed by archaea (1.67%), Eukaryota (0.63%), and viruses (0.7%). Metagenome guided CAZyme diversity of the microflora spanning across the confluence of Ganges-Yamuna River, could be harnessed for biomass and bioenergy applications.
Keywords: CAZymes; Confluence (Sangam); Lignocellulosic; River Ganges; River Yamuna

Spatio-temporal variation of the microbiome and resistome repertoire along an anthropogenically dynamic segment of the Ganges River, India - Samson, Rachel; Rajput, Vinay; Yadav, Rakeshkumar; Shah, Manan; Dastager, Syed; Khairnar, Krishna; Dharne, Mahesh (Science of the Total Environment, 2023)
Aquatic ecosystems are regarded as a hub of antibiotic and metal resistance genes. River Ganges is a unique riverine system in India with socio-cultural and economic significance. However, it remains underexplored for its microbiome and associated resistomes along its anthropogenically impacted course. The present study utilized a nanopore sequenc-ing approach to depict the microbial community structure in the sediments of the river Ganges harboring antibiotic and metal resistance genes (A/MRGs) in lower stretches known for anthropogenic impact. Comprehensive microbiome analyses revealed resistance genes against 23 different types of metals and 28 classes of antibiotics. The most dominant ARG category was multidrug resistance, while the most prevalent MRGs conferred resistance against copper and zinc. Seasonal differences dismally affected the microbiota of the Ganges. However, resistance genes for fosmidomycin and tetracycline varied with season ANOVA, p < 0.05. Interestingly, 333 and 334 ARG subtypes were observed at all the locations in pre-monsoon and post-monsoon, respectively. The taxa associated with the dominant ARGs and MRGs were Pseudomonas and Burkholderia, which are important nosocomial pathogens. A substantial phage diversity for pathogenic and putrefying bacteria at all locations attracts attention for its use to tackle the dissemination of antibiotic and metal-resistant bacteria. This study suggests the accumulation of antibiotics and metals as the driving force for the emergence of resistance genes and the affiliated bacteria trafficking them. The present metagenomic as-sessment highlights the need for comprehensive, long-term biological and physicochemical monitoring and mitigation strategies toward the contaminants associated with ARGs and MRGs in this nationally important river.
Keywords: Antibiotics (ARGs); Bacteriophages; Heavy metals (MRGs); Metagenomics; Microbiome; River Ganges

Bacteriophages: status quo and emerging trends toward one health approach - Samson, Rachel; Dharne, Mahesh; Khairnar, Krishna (Science of The Total Environment, 2024)
The alarming rise in antimicrobial resistance (AMR) among the drug-resistant pathogens has been attributed to the ESKAPEE group (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumanii, Pseudomonas aeruginosa, Enterobacter sp., and Escherichia coli). Recently, these AMR microbes have become difficult to treat, as they have rendered the existing therapeutics ineffective. Thus, there is an urgent need for effective alternatives to lessen or eliminate the current infections and limit the spread of emerging diseases under the ``One Health'' framework. Bacteriophages (phages) are naturally occurring biological resources with extraordinary potential for biomedical, agriculture/food safety, environmental protection, and energy production. Specific unique properties of phages, such as their bactericidal activity, host specificity, potency, and biocompatibility, make them desirable candidates in therapeutics. The recent biotechnological advancement has broadened the repertoire of phage applications in nanoscience, material science, physical chemistry, and soft
Keywords: Antimicrobial resistance (AMR); Bacteriophages; One-health; Therapeutics commercialization

Characterization of a novel Tequatrovirus phage from pristine stretch of the Ganges River, India, in reducing bacterial load from sewage water - Samson, Rachel; Pawar, Ameya; Khairnar, Krishna; Dharne, Mahesh (Journal of Environmental Chemical Engineering, 2025)
Effective treatment of wastewater (WW) and its reuse is necessary to meet certain sustainable development goals and a circular economy. Escherichia coli is one of the primary contaminants in the WW, and its extra-intestinal occurrence poses a considerable threat under one health. This study is the first report of a novel broadspectrum phage (& fcy;ERS-1) isolated from a pristine stretch of the Ganges River in the biocontrol of E. coli, resistant to 3rd-and 4th generation cephalosporins and aztreonam. This is the first report of a phage from the Tequatrovirus genus to infect P. aeruginosa. The & fcy;ERS-1 could reduce the abundance of E. coli cells by 8.22 log10 CFU/mL <= 24 hrs. Additionally, phi ERS-1 disrupted the biofilm of E. coli with a reduction of 3.88 log10 CFU/mL. Further, phi ERS-1 could inhibit biofilm by multiple strains of E. coli (ATCC 8739, 25922, 43888) and multiple generaincluding E. coli ATCC 8739, Shigella boydii ATCC 9207, P. aeruginosa (ATCC 9027). The phage phi ERS-1 reduced bacterial counts in raw WW by 2 log10 CFU/mL and 4 log10 CFU/mL reduction in coliform-enriched WW in <= 24 hours. Overall, this study suggests that phi ERS-1 could be used as an effective alternative to be combined with other treatments for improving the quality of WW disposal and environmental health by reducing the bacterial load.
Keywords: Antibiofouling; Biofilm; Coliform; Ganges; Green approach; Phages; wastewater

Deciphering the comprehensive microbiome of glacier-fed Ganges and functional aspects: implications for one health - Samson, Rachel; Kumar, Shubham; Dastager, Syed; Khairnar, Krishna; Dharne, Mahesh (Microbiology Spectrum, 2025)
Glacier-fed rivers are significant ecological components of the river catchments, yet their microbial diversity and the associated antimicrobial potential remain underexplored. The Ganges is a glacier-fed river of immense cultural, religious, and ecological significance that supports over 400 million people downstream, providing essential water for agriculture, industry, and daily use. Despite its importance, the microbial community composition and antimicrobial potential, across its relatively pristine origin, remain largely underexplored. One possible explanation for this could be the lower microbial load in the upstream glacier-fed region, which likely results in a reduced DNA yield, insufficient for whole-metagenome sequencing, in contrast to the more biologically diverse and nutrient-rich lower reaches. In this study, we developed an efficient DNA extraction and amplification method using low-input DNA to sequence the microbiome from sediments of the glacier-fed Ganges River in pre-monsoon and post-monsoon over 2 years. Taxonomic and functional diversity of bacterial and viral (phage) communities were analyzed, together with the seasonal variations in their composition. Significant differences in microbial communities were observed in response to seasonal shifts (P < 0.05). During the dry season, Proteobacteria and Actinobacteria were predominant, while Bacteroidetes and Firmicutes were abundant post-monsoon (P < 0.05). The microbiome harbors potential for the biosynthesis of streptomycin, phenylpropanoid, penicillin, and cephalosporins. Bacteriophages from Podoviridae, Myoviridae, and Siphoviridae showed lytic potential against putrefying and pathogenic bacteria. This first comprehensive study on the glacier-fed Ganges River highlights significant seasonal shifts in microbial diversity. The initial insights into the functional profile of the bacterial and phage diversity offer opportunities to explore various natural compounds and enzymes to tackle antimicrobial resistance under the one-health canopy.
Keywords: Bacteriophages; glacier-fed-Ganges; Microbiome; Secondary metabolites; special properties